Spectral Radius Inequalities and applications - خلايفة ثورية-فطحيزة علي أمال (university of eloued جامعة الوادي, 2024)
في هذه المذكرة، قمنا بدراسة نصف القطر الطيفي تعاريف وخواص، حيث خصصنا جزء كبير لتعرف على هذا المفهوم الرياضي وعلاقته بنصف القطر الرقمي والنظيم من خلال عرض بعض المترجحات حول هذا الموضوع، في الأخير قدمنا بعض الأمثلة حول نصف القطر الطيفي لبعض المؤثرات أما المصفوفات فاستعملنا برنامج الماتلاب لحساب نصف القطر الطيفي للمصفوفات We concern this work to study the spectral radius definitions and properties, also some inequalities of spectral radius and their relation with the numerical radius and norm. Finally, we see some applications, some example of calculate the spectral radius of certain operators and Matlab program to calculate the spectral radius of certain matrıx
مدكرة ماستر رياضيات
Keywords: لطيف، نصف القطر الطيفي، نصف القطر الرقمي النظيم.; Spectrum. Spectral radius. Numerical radius; Norm